The effects of different ratios of dietary calcium and phosphorus on calcium, phosphorus and magnesium metabolism in the chicken - Francis, John Charles (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1972.